EXPLORING PEDIATRIC ACCEPTANCE OF MINI-TABLETS: A COMPREHENSIVE REVIEW OF KEY STUDIES AND FUTURE PERSPECTIVES - Mahesh Patil; Suankit Harane; Vinita Kale; Milind Umekar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This comprehensive review synthesizes key insights from a series of studies that examining acceptance and swallowability of mini tablets in pediatric populations. The summarized research systematically explores the acceptability, safety and swallowability of mini-tablets across diverse pediatric age groups. Noteworthy findings include high acceptability and swallowability of filmcoated mini tablets, positive outcomes in various pediatric populations, and the well-tolerated nature of mini tablets in children aged 6–23 months. Despite acknowledging limitations such as recruitment challenges, potential biases, and ethical constraints, the review emphasizes the significance of optimizing formulations and exploring alternatives for mini-tablets in pediatric pharmacotherapy. Future research recommendations include prioritizing multi-center studies, addressing potential biases, and delving into real-world scenarios to enhance the acceptance and utilization of mini tablets in pediatric medication administration.